Dream Recall, Nightmares, and Aggression-Related Dream Content in Patients with REM Sleep Behavior Disorder (RBD) - Jigalin, Ruben; Schredl, Michael (Sleep Science, 2025)
Patients with REM sleep behavior disorder (RBD) enact their dreams, leading to enhanced dream recall. They report more negative emotions in their dreams, recall retrospective nightmares more frequently, and often experience more aggressive dreams. This study aims to understand dream characteristics in REM sleep behavior disorder using both retrospective and prospective measures in a controlled sleep laboratory setting to address possible recall biases in retrospective dream recall frequency. The sample comprises 102 iRBD-diagnosed patients (21 women, 81 men; M = 64.08, SD = 11.27) and 208 healthy controls (136 women, 72 men; M = 30.08, SD = 12.03), all undergoing identical procedures of two consecutive nights in the sleep laboratory, enabling a robust comparative examination of dream patterns. Retrospective assessments revealed a higher frequency of dream recall in patients with iRBD, while no significant difference was observed in prospective assessments. Nightmares were also reported more frequently in retrospective assessments in iRBD patients compared to healthy controls. Aggressive dream content was more frequent in patients with iRBD compared to controls, a future prospective diary study might clarify whether this heightened aggression in dreams is related to waking-life traits.
Keywords: dream recall; nightmares; REM sleep behavior disorder; dream content; aggression